HONEY BUSINESS TRENDS AND STRATEGIC ORIENTATIONS OF MARKETING COOPERATION IN UKRAINE BEEKEEPING - Дударь, Тарас; Дударь, Владимир (SWorldJournal, 2020)
The main economic and environmental factors of demand for Ukrainian honey in the world market were identified, where due to the high quality properties of Ukrainian honey, consumer demand is growing dynamically and as a result, our country has become one